Strategic Appraisal United States Air and Space Power in the 21st Century - Khalilzad, Zalmay (RAND Corporation, 2002)
Change--in international relations, in technology, and in society as a whole--has become the idiom of our age. One example of these changes has been an increasing recognition of the value of air and space assets for handling nearly every contingency from disaster relief to war and, onsequently, increasing demand for such assets. These developments have created both challenges and opportunities for the U.S. Air Force. This, the fourth volume in the Strategic Appraisal series, draws on the expertise of researchers from across RAND to explore both the challenges and opportunities that the U.S. Air Force faces as it strives to support the nation's interests in a challenging technological and security environment.Contributors examine the changing roles of air and space forces in U.S.national security strategy, the implications of new systems and technologiesfor military operations, and the role of nuclear weapons in U.S. securitystrategy. Contributors also discuss the status of major modernizationefforts within the Air Force, and the bill of health of the Air Force, asmeasured by its readiness to undertake its missions both today and in thefuture.